(untitled) (The Research of Medical Science Review, 2025)
Background: Mesenteric cysts are rare, fluid-filled lesions that present diagnostic challenges. While histopathology is the gold standard for diagnosis, it is invasive and not always feasible. With advancements in ultrasound technology, there is increasing interest in its use as a non-invasive diagnostic tool. However the evidence was limited to international studies and local study on it. This study was designed to evaluate ultrasound's diagnostic accuracy compared to histopathology. Objective: To determine the diagnostics accuracy of ultrasound in diagnosing of mesenteric cyst taking histopathology as gold standard. Study Settings: This study was conducted at the Department of Diagnostic Radiology, The Children’s Hospital, Lahore, over 6 months period from 03/07/2024 to 02-01-2025. Material and Methods: After ethical approval, 100 eligible patients were enrolled with informed consent. Ultrasound exams were performed using Esoate and Samsung machines, with transducers of 7.5-12 MHz linear and 3.5 MHz curved array. A graded compression technique was applied to detect mesenteric vessels. Histopathological findings were the gold standard, with all exams conducted by one experienced radiologist and surgeries by one surgical team to reduce bias. Data analysis in SPSS included descriptive statistics, sensitivity, specificity, PPV, NPV, and stratified analysis for age, gender, cyst size, and weight. Results: The study included 100 participants with a mean age of 8.26 ± 2.75 years, 54% boys and 46% girls. Ultrasound detected mesenteric cysts in 53 participants (53%), and histopathology confirmed cysts in 55 participants (55%). Ultrasound sensitivity was 83.64%, specificity 84.44%, and accuracy 84.00%. Conclusion: In conclusion, ultrasound proved to be highly accurate for detecting mesenteric cysts, with a sensitivity of 83.64%, specificity of 84.44%, and overall accuracy of 84.00%. The results highlight ultrasound as a reliable diagnostic tool, showing consistent performance across various subgroups like age, gender, cyst size, and weight.